Chapter Il principe selvaggio (1695) de Francesco Silvani: una curiosa taracea de motivos del teatro áureo español - Antonucci, Fausta (Studi e saggi, 2020)
In this paper, I intend to find out which texts inspired the libretto by Francesco Silvani, Il principe selvaggio (1695), whose events, according to the author, are taken "from the Fasti of Castile". The examination of the plot leads to exclude the existence of a historiographic "source" as the mention of the Fasti would suggest, and to hypothesize instead a multiple literary intertextuality. It seems that Silvani was reminiscent of theatrical texts such as El príncipe de los montes, by Juan Pérez de Montalbán, Virtudes vencen señales, by Luis Vélez de Guevara, and a constellation of works by Pedro Calderón de la Barca (El monstruo de los jardines, La hija del aire, Hado y divisa de Leonido y de Marfisa).